Neural Network For Testing - Smetana, Bedřich (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This article describes basics of neural networks, specifically aimed at usage of freeware to test freeware for creation simple neural network. Discussion focuses on the use of generally available programs and problems with use of freeware applications. Attention is devoted to a comparison of real and theoretical conditions connected with practical computer support.
Keywords: neural network; Matlab; Simbrain